Response of Deep Soil Carbon Pools to Forest Management in a Highly Productive Andisol - Dietzen, Christiana A.; Marques, Eduardo R. G.; James, Jason N.; Bernardi, Rodolpho H. A. [UNESP]; Holub, Scott M.; Harrison, Robert B. (Soil Sci Soc Amer, 2017)
Soil contains more C than the atmosphere and plant biomass combined. Consequently, it is the most important long-term sink for C within terrestrial ecosystems. An understanding of the potential to induce C sequestration in soils through management is crucial in light of increasing anthropogenic CO2 emissions. Nevertheless, soil has historically been under-represented in C cycling research, especially regarding subsurface (>30 cm) layers and processes. Research on the effects of forest management practices on deep soil C has been lacking. To test the effects of biomass removal and vegetation control treatments on deep soil C, soils were sampled to a depth of 3 m at the Fall River Long-term Soil Productivity Site in western Washington State. Treatments were installed 15 yr previously in a complete randomized block design. No difference was found in total soil C among treatments, but there was significantly less (a = 0.10) C stored at the deepest interval measured (250-300 cm) in the plots with vegetation control (8.6 Mg C ha(-1)) than in those without (16.3 Mg C ha(-1)). These results suggest the stability of soil C pools at Fall River and indicate that more intensive management practices may not deplete C pools at this site, but imply that these deep soil pools may be more sensitive to change than shallow pools. Here, 58.2% of the soil C pool is located below 30 cm, which demonstrates that shallow sampling significantly underestimates soil C pools and highlights the importance of understanding processes that control deep soil C.